Impact of wildfire return interval on the ectomycorrhizal resistant propagules communities of a Mediterranean open forest. - Buscardo, Erika; Rodríguez-Echeverría, Susana; Martín, María P.; De Angelis, Paolo; Pereira, João Santos; Freitas, Helena (Fungal biology, 2010)
Ectomycorrhizal (ECM) fungi, in particular their spores and other resistant propagules, play an important role in secondary succession processes that facilitate regeneration after disturbance events. In this study, the effects of high and low wildfire frequencies (respectively short and long fire return intervals) on the resistant propagules communities (RPCs) of a Mediterranean open pine forest were compared. Soil samples were collected in four mountain sites with different fire return intervals and used to test ectomycorrhiza development in two hosts, Pinus pinaster and Quercus suber. RPCs were characterized by direct sequencing of fungal internal transcribed spacer (ITS) regions from individual ECM root tips. Eighteen ECM species were detected in the bioassay. The most frequently found fungi were Cenococcum geophilum, Inocybe jacobi, Thelephora terrestris, Tomentella ellisii on both hosts and Rhizopogon luteolus and R. roseolus on maritime pine. A short fire return interval reduced the species richness of the ECM community found on Q. suber, promoted species like R. roseolus and reduced the abundance of other species (e.g. R. luteolus). The abundance of I. jacobi was positively affected by long fire return interval, but decreased significantly with recurrent fires. These results indicate that changes in fire frequency can alter the structure, composition and diversity of ECM communities, which could compromise the resilience of the ecosystem in highly disturbed areas.
The following values have no corresponding Zotero field: accession-num: 20943174
Keywords: Ectomycorrhizal resistant propagules community; Fire return interval; Mediterranean ecosystem; Pinus pinaster (maritime pine); Quercus suber (cork oak); succession